Effect of muscle load tasks with maximal isometric contractions on oxygenation of the trapezius muscle and sympathetic nervous activity in females with chronic neck and shoulder pain - Shiro Yukiko (BMC Musculoskeletal Disorders, 2012)
Abstract Background Sympathetic nervous activity contributes to the maintenance of muscle oxygenation. However, patients with chronic pain may suffer from autonomic dysfunction. Furthermore, insufficient muscle oxygenation is observed among workers with chronic neck and shoulder pain. The aim of our study was to investigate how muscle load tasks affect sympathetic nervous activity and changes in oxygenation of the trapezius muscles in subjects with chronic neck and shoulder pain. Methods Thirty females were assigned to two groups: a pain group consisting of subjects with chronic neck and shoulder pain and a control group consisting of asymptomatic subjects. The participants performed three sets of isometric exercise in an upright position; they contracted their trapezius muscles with maximum effort and let the muscles relax (Relax). Autonomic nervous activity and oxygenation of the trapezius muscles were measured by heart rate variability (HRV) and Near-Infrared Spectroscopy. Results Oxyhemoglobin and total hemoglobin of the trapezius muscles in the pain group were lower during the Relax period compared with the control group. In addition, the low frequency / high frequency (LF/HF) ratio of HRV significantly increased during isometric exercise in the control group, whereas there were no significant changes in the pain group. Conclusions Subjects with neck and shoulder pain showed lower oxygenation and blood flow of the trapezius muscles responding to isometric exercise, compared with asymptomatic subjects. Subjects with neck and shoulder pain also showed no significant changes in the LF/HF ratio of HRV responding to isometric exercise, which would imply a reduction in sympathetic nervous activity.